2021
DOI: 10.3389/fonc.2021.764618
|View full text |Cite
|
Sign up to set email alerts
|

Progress in the Application of Immune Checkpoint Inhibitor-Based Immunotherapy for Targeting Different Types of Colorectal Cancer

Abstract: Colorectal cancer (CRC), a common malignant disease, has the second highest mortality rate among all cancer types. Due to the diversity and heterogeneity of CRC, few effective treatment strategies have been developed in recent years, except for surgical resection. As immunotherapy has become a revolutionary treatment after surgery, along with chemoradiotherapy and targeted therapy, numerous basic research studies and clinical trials have been conducted on CRC. Therefore, immune checkpoint inhibitor (ICI) thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 153 publications
0
13
0
Order By: Relevance
“…However, in treatment studies targeting mCRC, PD-L1 expression on tumor or immune cells has not been associated with ICI responses ( 30 32 ). Additionally, several other factors such as TMB ( 33 ), MSI ( 34 ), somatic copy-number alterations ( 35 ), T cell signaling ( 36 ), human leukocyte antigen (HLA) class I genotype ( 37 ), and TGFβ signaling ( 20 ) have been shown to correlate with the clinical outcome of ICIs therapy, based on molecular profiling of cancers treated with different immunotherapies. Unlike conventional cancer therapies, ICIs do not directly kill tumor cells; instead, they affect tumor cells through the patient’s immune system or the TME.…”
Section: Discussionmentioning
confidence: 99%
“…However, in treatment studies targeting mCRC, PD-L1 expression on tumor or immune cells has not been associated with ICI responses ( 30 32 ). Additionally, several other factors such as TMB ( 33 ), MSI ( 34 ), somatic copy-number alterations ( 35 ), T cell signaling ( 36 ), human leukocyte antigen (HLA) class I genotype ( 37 ), and TGFβ signaling ( 20 ) have been shown to correlate with the clinical outcome of ICIs therapy, based on molecular profiling of cancers treated with different immunotherapies. Unlike conventional cancer therapies, ICIs do not directly kill tumor cells; instead, they affect tumor cells through the patient’s immune system or the TME.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, three representative ICIs have been commonly applied in clinical practice, including programmed cell death 1 (PD-1), programmed cell death ligand 1 (PD-L1), and cytotoxic drug T lymphocyte-associated antigen 4 (CTLA-4) inhibitors (1). However, despite encouraging results from clinical trials and the real world, a fairly large proportion of patients fail to benefit from ICI therapy due to various inherent and environmental factors, such as microsatellite instability, gut microbiota, and concomitant medications (2)(3)(4). Previously, our team has demonstrated that antibiotic administration shortly before or after ICI treatment is associated with poor clinical outcomes in patients with advanced solid cancers (5).…”
Section: Introductionmentioning
confidence: 99%
“…PD-1 and PD-L1 are a pair of important immune checkpoint (ICs) that work as the brake on the immune system and play a crucial role in the tumor immune escaping process (35). After the binding of PD-1 and PD-L1, tumor cells take advantage of the recognition of the T-cell receptor, further suppressing immunity and evading immune surveillance (36). In 2002, the evidence that the PD-1 pathway mediating tumor immunity was first reported in that the overexpression of PD-L1 will weaken the cytolytic activity of T cells and then significantly promote the occurrence and invasion of tumors (37).…”
Section: Mechanisms Of Anti-pd-1/pd-l1 Therapymentioning
confidence: 99%